Comparison of Eulerian QBMM and classical Eulerian–Eulerian method for the simulation of polydisperse bubbly flows. Issue 11 (31st July 2019) - Li, Dongyue; Marchisio, Daniele; Hasse, Christian; Lucas, Dirk
Abstract: The spatial gas distribution of poly‐disperse bubbly flows depends greatly on the bubble size. To reflect the resulting polycelerity, more than two momentum balance equations (typically for the gas and liquid phases) have to be considered, as done in the multifluid approach. The inhomogeneous multiple‐size group model follows this approach, also combined with a population balance model. As an alternative, in a previous work, an Eulerian quadrature‐based moments method (E‐QBMM) was implemented in OpenFOAM; however, only the drag force was included. In this work, different nondrag forces (lift, wall lubrication, and turbulent dispersion) are added to enable more complex test cases to be simulated. Simulation results obtained using E‐QBMM are compared with the classical E–E method and validated against experimental data for different test cases. The results show that there is good agreement between E‐QBMM and E–E methods for mono‐disperse cases, but E‐QBMM can better simulate the separation and segregation of small and large bubbles.